An MRAS Speed Observer Based on dq-axis Power Winding Flux for Sensorless Control of Standalone BDFIGs - K. Ebraheem, Alameen; Eldin Idris, Elnail Kamal; Senior, Wei Xu; Liu, Yi; Zhu, Jianguo (Journal of Advanced Industrial Technology and Application, 2022)
This paper addresses a new mechanical rotor speed observer for sensorless control of standalone Brushless Doubly-Fed Induction Generators (BDFIGs) based on the dq axis power winding flux model reference adaptive system (MRAS) observer. The observer is integrated in the control method for control the terminal frequency and voltage magnitude under various work conditions. The efficiency of the proposed observer and control strategy is proved by overall simulation results and confirmed by experiments. As illustrated without using physical rotor speed sensors, the sensorless control strategy integrating the proposed speed observer can keep effectively the frequency and amplitude of power winding voltage fixed at various rotor speeds and under various conditions of machine parameter and load changes.